Design, User Experience, and Usability. Web, Mobile, and Product Design Second International Conference, DUXU 2013, Held as Part of HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013, Proceedings, Part IV - Marcus, Aaron; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The four-volume set LNCS 8012, 8013, 8014 and 8015 constitutes the proceedings of the Second International Conference on Design, User Experience, and Usability, DUXU 2013, held as part of the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, USA in July 2013, jointly with 12 other thematically similar conferences. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The total of 282 contributions included in the DUXU proceedings were carefully reviewed and selected for inclusion in this four-volume set. The 83 papers included in this volume are organized in the following topical sections: DUXU in business and the enterprise, designing for the Web experience; product design; information and knowledge design and visualisation; and mobile applications and services.
DUXU in business and the enterprise -- Designing for the Web experience -- Product design -- Information and knowledge design and visualisation -- Mobile applications and services.
Keywords: Computer science; Information storage and retrieval systems; Computer Science; User Interfaces and Human Computer Interaction; Computer Applications; Computers and Society; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Models and Principles